Anesthetic Isoflurane Posttreatment Attenuates Experimental Lung Injury by Inhibiting Inflammation and Apoptosis - Jun-tang Li; Hui Wang; Wei Li; Li-feng Wang; Li-chao Hou; Jing-lan Mu; Xin Liu; Hui-juan Chen; Ke-lang Xie; Nan-lin Li; Chun-fang Gao (Hindawi Limited, 2013)
We investigated the effect of 1.4% isoflurane (ISO) on the development of inflammation and apoptosis caused by zymosan (ZY) in mice. We found that ZY-challenged mice exhibited significant body weight loss, markedly high mortality, and significant lung injury characterized by the deterioration of histopathology, histologic scores, and wet-to-dry ratio after ISO treatment. ISO dramatically attenuated ZY-induced lung neutrophil recruitment and inflammation, as evidenced by the reduced levels of total cells, neutrophils, and proinflammatory cytokines (i.e., tumor necrosis factor-α, interleukin- (IL-) 1β, IL-6, and macrophage inflammatory protein-2) in bronchoalveolar lavage fluid and of their mRNA expression in lung tissues. ISO also inhibited ZY-induced expression and activation of nuclear factor-kappaB p65 and inducible nitric oxide synthase in pulmonary tissue. ZY administration also resulted in the upregulation of heme oxygenase-1 expression and activity in the lung, which was further enhanced by ISO treatment. Moreover, ISO markedly prevented ZY-induced pulmonary cell apoptosis in mice, as reflected by the decrease in expression of procaspase-8, procaspase-3, cleaved caspase-8, and cleaved caspase-3, as well as in caspase-3 activity and Bcl-2-associated X/B-cell lymphoma 2 ratio. These results indicate that ISO is a potential therapeutic drug for treating ZY-induced lung injury, and further investigations are warranted.